2019
DOI: 10.21203/rs.2.12707/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential for non-combustible nicotine products to reduce socioeconomic inequalities in smoking: a systematic review and synthesis of best available evidence

Abstract: Background While some experts have emphasised the potential for e-cigarettes to facilitate cessation among smokers with low socioeconomic status (SES), there is limited evidence of their likely equity impact. We assessed the potential for electronic cigarettes and other non-combustible nicotine-containing products (NCNPs) to reduce inequalities in smoking by systematically reviewing evidence on their use by SES in countries at stage IV of the cigarette epidemic. Methods Ten electronic databases were searche… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 79 publications
(93 reference statements)
1
9
0
1
Order By: Relevance
“…This review is part of a larger project and the results of a literature review on quantitative data are reported in a separate paper [7]. A full protocol of this project, including the quantitative and qualitative reviews, has been registered with PROSPERO (ID: CRD42017080672) [37].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This review is part of a larger project and the results of a literature review on quantitative data are reported in a separate paper [7]. A full protocol of this project, including the quantitative and qualitative reviews, has been registered with PROSPERO (ID: CRD42017080672) [37].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, quantitative data continues to demonstrate a concentration of smoking within socioeconomically disadvantaged communities across Europe [6]. A recent systematic review of quantitative evidence, conducted by the authors of this review, found limited evidence that non-combustible nicotine products (NCNP) had reduced or are likely to reduce socioeconomic inequalities in smoking [7]. The quantitative review included all types of NCNP, including e-cigarettes, in order to explore differential potential for reducing inequalities of the wide range of products that now exists.…”
Section: Introductionmentioning
confidence: 98%
“…This review is part of a larger project and the results of a literature review on quantitative data are reported in a separate paper [7]. A full protocol of this project, including the quantitative and qualitative reviews, has been registered with PROSPERO (ID: CRD42017080672) [38].…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review of quantitative evidence, conducted by the authors of this review, found limited evidence that non-combustible nicotine products (NCNP) had reduced or are likely to reduce socioeconomic inequalities in smoking [7]. The quantitative review included all types of NCNP, including ecigarettes, in order to explore differential potential for reducing inequalities of the wide range of products that now exists.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, quantitative data continues to demonstrate a concentration of smoking within socioeconomically disadvantaged communities across Europe [6]. A recent systematic review of quantitative evidence, conducted by the authors of this review, found limited evidence that non-combustible nicotine products (NCNP) had reduced or are likely to reduce socioeconomic inequalities in smoking [7]. The quantitative review included all types of NCNP, including ecigarettes, in order to explore differential potential for reducing inequalities of the wide range of products that now exists.…”
Section: Introductionmentioning
confidence: 98%